Business models for integration of sustainability in universities: An explorative analysis of Italian state universities. (15th November 2021) - Giovanelli, Lucia; Rotondo, Federico; Ezza, Alberto
Abstract: Although the leadership role of higher education in creating a sustainable development has been widely recognized, there is a paucity of studies following a strategic perspective to explain how universities integrate sustainability in the different areas of their activity to gain a competitive advantage and contribute to the sustainable development of a broad range of stakeholders. More empirical research on the design and implementation of strategies and operations developed by universities to re-orient themselves towards sustainability has also been required, as well as systemic frameworks for evaluating sustainability performance in higher education. This paper addresses these gaps by proposing a conceptual framework for diagnosis of the integration of sustainability in universities from a strategic perspective. In particular, the concept of a sustainable business model is first contextualized to higher education and then used for interpreting the core logic through which universities create value for themselves, society and the environment. In order to assess the applicability and usefulness of this framework, a cluster analysis of all the 61 Italian state universities is used to identify business models with different degrees of strategic orientation towards sustainability and to start discussing the relationships between sustainable business models and university size, geographic location and performance. Highlights: Higher education has a key role in creating sustainable development. A conceptual framework of university sustainable business models is developed. Universities are grouped on the basis of their shared-value creation processes. Analysis revealed six models reflecting a different approach to sustainability.